3D Au–SiO2 nanohybrids as a potential scaffold coating material for neuroengineering. Issue 53 (16th May 2016) - Kundu, Paromita; Belu, Andreea; Neumann, Elmar; Mayer, Dirk; Offenhäusser, Andreas
Abstract : We demonstrate 3D Au–SiO2 hybrid nanoparticles render micro/nanotopography and provide a high density of stable adhesion cue domains facilitating strong adhesion, viability and guidance of the neurons. Abstract : We demonstrate the potential application of chemically synthesized 3D Au–SiO2 hybrid nanoparticles as a promising candidate for scaffold designing in neuroengineering. The hybrid nanospheres on substrates provide micro/nanotopography and the fine Au nanoparticles immobilized on SiO2 spheres together provide stable adhesion cue domains facilitating adhesion and viability of the cells as well as guidance of neurites. We also investigated the cell–nanohybrid interface and interaction mechanism by FIB-SEM for a better insight into the mode of adhesion.